Multiple Electronic Phases Coexisting under Inhomogeneous Strains in the Correlated Insulator - Baofei Hou; Yu Zhang; Teng Zhang; Jizheng Wu; Quanzhen Zhang; Xu Han; Zeping Huang; Yaoyao Chen; Hongyan Ji; Tingting Wang; Liwei Liu; Chen Si; et al. (Advanced Science, 2023)
Abstract Monolayer transition metal dichalcogenides (TMDs) can host exotic phenomena such as correlated insulating and charge‐density‐wave (CDW) phases. Such properties are strongly dependent on the precise atomic arrangements. Strain, as an effective tuning parameter in atomic arrangements, has been widely used for tailoring material's structures and related properties, yet to date, a convincing demonstration of strain‐induced dedicate phase transition at nanometer scale in monolayer TMDs has been lacking. Here, a strain engineering technique is developed to controllably introduce out‐of‐plane atomic deformations in monolayer CDW material 1T‐NbSe2. The scanning tunneling microscopy and spectroscopy (STM and STS) measurements, accompanied by first‐principles calculations, demonstrate that the CDW phase of 1T‐NbSe2 can survive under both tensile and compressive strains even up to 5%. Moreover, significant strain‐induced phase transitions are observed, i.e., tensile (compressive) strains can drive 1T‐NbSe2 from an intrinsic‐correlated insulator into a band insulator (metal). Furthermore, experimental evidence of the multiple electronic phase coexistence at the nanoscale is provided. The results shed new lights on the strain engineering of correlated insulator and useful for design and development of strain‐related nanodevices.